Joint Effects of Developmental Stage and Water Deficit on Essential Oil Traits (Content, Yield, Composition) and Related Gene Expression: A Case Study in Two Thymus Species - Yousefzadeh, Kazem; Houshmand, Saadollah; Shiran, Behrouz; Mousavi-Fard, Sadegh; Zeinali, Hossein; Nikoloudakis, Nikolaos; Gheisari, Mohammad Mehdi; Fanourakis, Dimitrios (My University, 2022)
In this study, the joint effects of developmental stage and soil water availability on biomass accumulation, harvest index, as well as essential oil content, yield and composition were investigated in Thymus armeniacus. For comparison purposes, Thymus kotschyanus was also considered. Plants were irrigated to either 75 or 50% of field capacity, and were sampled at 50 or 100% blooming. In both species, water deficit exerted limited effect on the time required to initiate or complete flowering. In most critical aspects of yield (harvestable organs dry weight, essential oil yield), T. armeniacus was found to be superior than T. kotschyanus. In these traits, however, T. armeniacus underwent a more drastic water deficit-induced decrease. Across treatments, metabolite levels fairly correlated to transcript accumulation profiles of terpene synthases and cytochrome P450 genes. Indices affiliated with reactive oxygen species were inter-correlated with the activity of five major antioxidant enzymes, while the same was noted between leaf water status and pigment content. Taken together, these results indicate that when water availability can be achieved, higher yields will be obtained by cultivation of T. armeniacus. Under water deficit conditions, instead, the more drought tolerant T. kotschyanus stands out as the primary choice.
Keywords: blooming; harvest index; terpene; Thymus armeniacus; Thymus kotschyanus; water deprivation